KAJIAN TOUR TABERNAKEL IMPLEMENTASI PERJALANAN DOA DARI PELATARAN KE RUANG MAHA KUDUS - Erlyna, Erlyna (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
The Tabernacle, established by Moses at God's command in the wilderness, was His holy dwelling place, signified by the pillar of cloud and fire. As the center of worship in the Old Testament, the Tabernacle featured a divinely designed structure: the outer court with the Altar of Burnt Offering and the Laver; the Holy Place containing the Table of Showbread, the Golden Lampstand, and the Altar of Incense; and the Most Holy Place housing the Ark of the Covenant with the mercy seat. Though historically exclusive to Israel, the spiritual meaning of the Tabernacle remains relevant for believers today. In the era of grace, every believer is a priest with direct access to God through Christ. This study explores the application of the "Tabernacle Tour" as a guide for personal prayer, where each piece of furniture symbolizes a spiritual stage from confession of sin to intimate communion with God. Through biblical reflection and practical experience, the author finds that this symbolic journey helps believers experience quality time with the Lord in prayer, transforming the Tabernacle from a historical reality into a living spiritual model for faith growth and contemporary worship.